Re-imagining the Gothic in Contemporary Australia: Carmel Bird Discusses Her Mandala Trilogy - Britten, Naomi (American Association of Australian Literary Studies, 2010)
Presents an interview with Australian author Carmel Bird is presented. She discusses whether she consciously chose to write the "Mandela Trilogy," which includes the books "The White Garden," "Red Shoes" and "Cape Grimm," the intertextuality of "Mandela," and how the concept of charisma and the power that certain individuals possess over others forms a link between "White Garden," "Red" and "Cape" together.